2015
DOI: 10.1002/2015wr017633
|View full text |Cite
|
Sign up to set email alerts
|

Accepting managed aquifer recharge of urban storm water reuse: The role of policy‐related factors

Abstract: A between-groups experimental design examined public acceptance for managed aquifer recharge of storm water for indirect potable and nonpotable reuse; acceptance was based on five policyrelated variables (fairness, effectiveness, trust, importance of safety assurances, and importance of communication activities). Results showed that public acceptance (N 5 408) for managed aquifer recharge of storm water was higher for nonpotable applications, as was the importance of safety assurances. Analyses of variance als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, these findings must be tempered against the fact that potable reuse schemes, when considered on their own terms (rather than compared against other hypothetical uses), can still generate high levels of support (City of San Diego 2013, Hills et. al 2013, Aitken et al 2014, Mankad & Walton 2015). Hartley's (2006) list of ten factors also stated that public acceptance of reuse is more likely when protection of the environment is a clear benefit; when promotion of water conservation is a clear benefit; and when awareness of water supply problems in the community is high.…”
Section: Identifying the Factors That Influence Public Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these findings must be tempered against the fact that potable reuse schemes, when considered on their own terms (rather than compared against other hypothetical uses), can still generate high levels of support (City of San Diego 2013, Hills et. al 2013, Aitken et al 2014, Mankad & Walton 2015). Hartley's (2006) list of ten factors also stated that public acceptance of reuse is more likely when protection of the environment is a clear benefit; when promotion of water conservation is a clear benefit; and when awareness of water supply problems in the community is high.…”
Section: Identifying the Factors That Influence Public Reactionsmentioning
confidence: 99%
“…As previously mentioned, several modelling-based studies have argued that higher levels of trust are associated with lower perceptions of risk, which in turn increase the likelihood of acceptance (Nancarrow et al 2009, Bratanova et al 2013, Ross et al 2014. In addition, a large number of studies from different approaches have found that trust is actually one of the most important factors in determining the acceptance of water reuse (Ormerod & Scott 2013, Aitken et al 2014, Ross et al 2014, Mankad & Walton 2015.…”
Section: Trust Risk Perceptions and Affective Reactionsmentioning
confidence: 99%
“…Partially as a function of practical attempts to implement recycled potable water programs, there has been increased research concerning the psychological and social factors associated with the acceptance of recycled water (Fielding et al, 2018; Smith et al, 2018). Factors associated with acceptance include being less disgust sensitive (Callaghan, Moloney, & Blair, 2012; Rozin, Haddad, Nemeroff, & Slovic, 2015; Wester et al, 2015), more educated (Price et al, 2015), more trusting (Mankad & Walton, 2015; Ormerod & Scott, 2013; Price et al, 2015), having more experience with recycled water (Dolnicar, Hurlimann, & Grun, 2011), and having more subjective knowledge of recycled water (Dolnicar et al, 2010; Dolnicar & Schafer, 2009; Fielding & Roiko, 2014).…”
Section: Psychological Factors Associated With Acceptance Of Recycledmentioning
confidence: 99%
“…Basic events that can lead to MAR failure were compiled based on a literature review of the problems encountered by different facilities around the world (Aiken and Kuniansky, 2002;Alazard et al, 2016;Assmuth et al, 2016;Bhusari et al, 2016;Chaoka et al, 2006;Flint and Ellett, 2005;Masetti et al, 2016;Murray and Ravenscroft, 2010;Petersen and Glotzbach, 2005;Schneider et al, 1987;Izbicki et al, 2006;Sultana and Ahmed, 2016;Tredoux et al, 2009;Tredoux and Cain, 2010;Tripathi, 2016). We revised 51 MAR facilities at 47 sites (some sites involved more than one facility) located in different countries and climatic conditions worldwide: Australia, Belgium, Botswana, China, Finland, France, Germany, India, Israel, Italy, Jordan, Namibia, South Africa, Spain, Tunisia, and USA.…”
Section: Introductionmentioning
confidence: 99%